(untitled) (International Journal of Applied Research in Management and Economics, 2023)
Governments derive a significant portion of their income from taxation. Collection of tax is however impeded by tax non-compliant activities as well as tax evasion. This necessitates measures to ensure tax compliance, such as tax audits. The study looked into the factors that influence taxpayers’ post-audit compliance behavior in Ghana, with the Ho and Hohoe Small Taxpayer Offices as a case study. The focus of the study was on the effectiveness of tax audit procedures, post-tax audit compliance behavior of taxpayers, and taxpayers’ experience with tax officers during and after the first tax audit. To achieve this aim, the study utilized the case study method of research. The researcher used the purposive sampling technique to select respondents for the questionnaire survey. The primary goal of the research was to investigate the efficacy of tax audit methods. The study identified that tax audit procedures were most effective in the Ho and Hohoe Small Taxpayer offices. The effectiveness of the audit procedures was ensured through the thorough examination of all relevant books and documents by skilled auditors. The second purpose of the study was to investigate the post-tax audit compliance behaviour of taxpayers. The study found that, after the audit procedures, taxpayers started filing tax returns accurately and timely. This improvement was primarily due to the level of education provided by tax officers during tax audits. Finally, the last objective sought to examine taxpayers’ experience with tax officers during and after the first tax audit. The study found that there were very few cases (11.40%) where respondents agreed that auditors compelled them to do something to reduce the tax. However, tax officers endeavored to provide legal backing and explanation for every decision made. The learning process that tax officers took taxpayers through has built a cordial relationship between the two parties. Tax audits, when structured to ensure proper collection of taxes, can lead to minimal tax avoidance and tax evasion and strict compliance with the applicable tax laws, and an enhanced degree of voluntary tax compliance.